2022
DOI: 10.2147/idr.s388816
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1C in-House RNA-Based Genotyping Assay for Detection of Drug Resistance Mutations in Samples with Low-Level Viral Loads

Abstract: Monitoring HIV-1 drug resistance mutations (DRM) in treated patients on combination antiretroviral therapy (cART) with a detectable HIV-1 viral load (VL) is important for the selection of appropriate cART. Currently, there is limited data on HIV DRM at low-level viremia (LLV) (VL 401-999 copies/mL) due to the use of a threshold of VL ≥1000 copies/mL for HIV DRM testing. We here assess the performance of an in-house HIV drug resistance genotyping assay using plasma for the detection of DRM at LLV. Methods: We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Using in-house genotypic resistance testing ( Seatla et al, 2019 ; Bareng et al, 2022 ), the extracted RNA was amplified by nested Polymerase chain reaction (PCR) to obtain the HIV-1 pol which comprised the entire protease (PR) gene (codons 1-99) and reverse transcriptase (RT) gene (codons 1-560). The RT-PCR was done using the following primers ( Rowley et al, 2016 ; Bareng et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using in-house genotypic resistance testing ( Seatla et al, 2019 ; Bareng et al, 2022 ), the extracted RNA was amplified by nested Polymerase chain reaction (PCR) to obtain the HIV-1 pol which comprised the entire protease (PR) gene (codons 1-99) and reverse transcriptase (RT) gene (codons 1-560). The RT-PCR was done using the following primers ( Rowley et al, 2016 ; Bareng et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Both one-step RT-PCR and nested PCR amplifications were carried out in the Applied Biosystems 2,720 Thermal Cycler. The RT-PCR was performed using Roche one-step transcriptor enzyme while the nested PCR was done using Phusion High Fidelity enzyme ( Rowley et al, 2016 ; Bareng et al, 2022 ; Kelentse et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the VL falls below 1000 copies/mL, the amplification success rate for drug resistance testing by genotyping will be low. In contrast, studies identified drug‐resistant mutations (DRMs) even in LLV, and the presence of DRMs in LLV strongly predicted subsequent VF [23, 24]. HIV RNA genotyping resistance testing (GRT) may not be a reliable option for PLWH with LLV due to the possibility of results being inaccurate with HIV RNA <500 copies/mL or < 1000 copies/mL [13, 25].…”
Section: Llv: Definition and Clinical Implicationsmentioning
confidence: 99%
“…DHHS guidelines suggest GRT in viral levels above 1000 copies/mL and warn that GRT taken within 500–1000 copies/mL may be unsuccessful [13]. DRMs have been reported at variable percentages in different studies [23]. Results from a multicentre cohort study in Europe found that of 1654 individuals experiencing LLV, 140 (8%) underwent a registered resistance test within 90 days of the first VL recorded during LLV, and of these 49 (35%) had DRMs ≥1 [20].…”
Section: Llv: Definition and Clinical Implicationsmentioning
confidence: 99%